FINANCIAL DEVELOPMENT AND ECONOMIC GROWTH - L. L. Igonina (Финансы: теория и практика)
Modern development challenges of economic development of Russia in the face of increasing financial constraints determines the need to for the formation of the financial system, designed to create the necessary conditions for sustainable economic dynamics that are updated by the scientific development issues influence the level of financial development on economic growth. The paper generalizes the results of theoretical and empirical research on the financial sector role in the economy. We have shown that due to the co-evolution of finance and economy the financial sector could be both a factor of economic growth, and a source of economic instability. The paper proves a comprehensive approach to the study of financial development, including the allocation of its qualitative and quantitative characteristics. We have analyzed the financial development in Russian economy with the group of indicators that are based on a system of parametric estimates of the World Bank experts and take into account the structural and functional features of the domestic financial system.The results allowed to identify the most significant financial determinants of economic growth and justify the key policy areas of the domestic financial sector.